Case Report: Talaromyces marneffei infections associated with pharyngeal and laryngeal injuries in three children with aberrant innate immunity: a case series - Zhang, Changhao; Lu, Gen; Xu, Xuehua; Fan, Huifeng (Frontiers in Pediatrics, 2025)
BackgroundTalaromyces marneffei (T. marneffei) is a pathogenic yeast that causes high fatality rates among immunocompromised individuals. The organism appears to target the lungs, liver, gut-associated lymphoid tissues, lymph nodes, spleen, bone marrow, kidneys, and the tonsils in the affected individuals. Evidence suggests that the lungs and liver are seriously injured in T. marneffei infections. Injuries to the pharyngeal and laryngeal compartments have seldom been reported.Case presentationThree pediatric patients with T. marneffei infections were admitted to the Guangzhou Women and Children's Center between August 2015 and March 2023. All three children showed evidence of pharyngeal and laryngeal injuries.ConclusionsDamage to the pharyngeal and laryngeal compartments appears to be an important clinical manifestation among HIV-negative pediatric individuals with a T. marneffei infection.